ANALYSIS OF STUDENT LEARNING DIFFICULTIES REVIEWED FROM THE ASPECT OF COGNITIVE PROCESSES - Nurul; Wendi Kusriandi; Neneng Aminah (Cirebon International Conference on Education and Economics Proceeding, 2024)
Learning difficulties in mathematics can be a significant obstacle in a student’s academic achievement and can affect their self-confidence in terms of their mathematical abilities. This phenomenon requires a deep understanding of the cognitive processes involved in mathematics learning. By understanding the cognitive aspects underlying mathematics learning difficulties, we can identify effective intervention strategies to help students overcome their difficulties. This research aims to explore the analysis of students’ mathematics learning difficulties by considering aspects of the cognitive processes involved. The cognitive process here refers to the assessment preparation guide which consists of connecting with previous knowledge, making connections in the text, making inferences, vocabulary, summarizing the text, mathematical thinking, multimodal literacy, and metacognition. This type of research is descriptive qualitative research. Namely research that is described through writing and words. The data collection technique in this research was a diagnostic test on Opportunity material in class XII MIPA 2, totaling 34 students. Based on research results, most students still do not have sufficient ability to use previous knowledge in understanding a text. Strengthening material concepts and skills is highly prioritized in learning, especially in linking the relationship between existing knowledge and text content, and strategies are needed to apply this knowledge.